(untitled) (International Journal of Studies in Nursing, 2023)
Self-care is defined as taking time to participate in activities that promote personal physical health, mental health, and wellness. Nursing students worldwide have been found to be deficient in self-care. A pilot project was developed to provide a variety of wellness-related activities throughout one academic school year for students in an undergraduate nursing program in the United States, in an effort to promote self-care practices. The students were surveyed on their perception of self-care activities covering six major domains, such as physical activity and health promotion. They were also asked qualitative questions about their understanding of self-care and its importance in nursing via focus groups. At the end of the school year, the students repeated the survey, and were asked to provide feedback on the activities selected. The purpose of this article is to discuss the findings of the post-intervention implementation. There were no statistical changes in the students’ self-care survey results. However, anecdotal evidence revealed that the students, as a whole, felt that the activities were helpful in promoting personal well-being, appreciated support from faculty, and reported a desire for the activities to continue.